Four heterozygous de novo variants in ASXL3 identified with Bainbridge–Ropers syndrome and further dissecting published genotype–phenotype spectrum - Ling, Shengjie; Zhang, Yiming; Li, Ning; Tian, Shan; Hu, Rui; Zhang, Dongdong; Guo, Weitong (Frontiers in Neuroscience, 2024)
Bainbridge–Ropers syndrome (BRPS) is a recently described neurodevelopmental genetic disorder associated with de novo truncating variants in additional sex combs like 3 (ASXL3) on chromosome 18q12.1. Trio-based exome sequencing was conducted on patients admitted to the Children’s Hospital Affiliated to Shandong University and diagnosed with unexplained intellectual disabilities or developmental delay between June 2022 and January 2024. De novo truncation of ASXL3 was identified in four patients, and the pathogenic variants and their de novo status were validated using Sanger sequencing. Comprehensive clinical phenotype–genotype information of all previously reported patients with BRPS was collected and summarized. The common clinical manifestations observed in the four patients included language and intellectual disabilities or psychomotor retardation. Genetic analysis revealed that patient 1 carried a de novo heterozygous variant, c.1667_1668del (p.Thr556Arpfs*3), whereas patient 2 had a novel heterozygous frameshift variant of ASXL3, c.3324del (p.Lys1109Serfs*34). These two variants have not been documented to date. Additionally, patients 3 and 4 exhibited a de novo variant, c.4678C > T (p.Arg1560Ter). Based on the combined assessment of clinical phenotypes and genetic testing results, it was postulated that all four children presented with BRPS syndrome caused by pathogenic variations in ASXL3. The present study complements the range of ASXL3 mutational and phenotypic spectra in the population, highlighting subtle distinctions in clinical manifestations between Chinese patients and other racial groups. The reporting of additional cases will contribute to further elucidating the function of ASXL3 and establishing a solid foundation for clinical diagnosis and treatment.